Modernization of Higher Education in Central Asian Countries: Trends, Problems and Solutions - Anichkin, Eugene S.; Kovalenko, Kseniya E. (Journal of History Culture and Art Research, 2018)
This study examines key transformations in the development of higher education in the countries of Central Asia, conditioned by the processes of globalization. The study reveals the general tendencies of the modernization of higher education in Central Asian countries: the restructuring of the university system, the expansion of the mechanisms for assessing and monitoring the activities of higher education institutions, the practical orientation of education, the expansion of the network interaction of higher education institutions and the formation of university associations, the internationalization of educational activity, the virtualization of the educational process. In conclusion, the main problems of cooperation in the formation of the educational landscape of the Central Asian countries are considered and ways of their solution are suggested.